Private spending on children's education: Low-income families pay relatively more - Carsten Schröder; C. Katharina Spieß; Johanna Storck (DIW Economic Bulletin, 2015)
Education is not financed solely by the taxpayer-many institutions and activities require payment of top-up fees, at the very least. This applies for instance to education and care services for children. A household's private expenditure on education depends largely on the families' available financial resources. However, to date, very little research has been conducted on the relationship between income and expenditure on education. The present study by DIW Berlin is based on data from the Socio-Economic Panel (SOEP) study and the SOEP-related study, Families in Germany (Familien in Deutschland, FiD) for 2012. The present work analyzes private spending on various educational provisions such as child daycare services, private schools, or non-formal educational programs, i.e. sports clubs or music schools. The findings of the study indicate that, of the families who actually spend money on their children's education, it is the low-income households that use a higher share of their household budget for this purpose-this applies both to overall education expenditure and to spending on individual educational services. However, if we consider all family households in Germany, higher-income families spend more on education, both in absolute and relative terms. Furthermore, it also holds true that the younger the children, the higher the share of the household's income spent on education. More progressive fee scales could help reducing expenditure burdens of low-income families and support children to make full use of their educational potentials.
Keywords: D12; D39; H52; I2; 330; education; private expenditures; income distribution; costs for children